Vertiy O. I. “…and how difficult is to be a man in our time” (from the correspondence of Joseph Dudka, Mykola Danko, Leonid Maletsky and Petro Rotach) - Vertiy O. I. (Philological Treatises, 2020)
The publication contains correspondence of the poet and teacher J. Dudka (was born in the village Shiroky Yar, Romny district of Sumy region), who was persecuted by the Soviet regime, with M. Danko, L. Maletsky and P. Rotach. It describes the spiritual world of the authors, their public position in 60s – early 90s of the twentieth century.